(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
this article examines the intricate relationship between innovation management and economic growth, utilizing Uzbekistan as a case study to illustrate how strategic policy reforms and technological advancements have propelled the nation’s transition from a resource-dependent economy to one increasingly driven by knowledge and creativity. Drawing on empirical data from recent years, it highlights Uzbekistan’s implementation of innovation parks, research and development incentives, and public-private partnerships, which have contributed to an average annual GDP growth of 5.3% since 2017, while also addressing persistent challenges such as inadequate funding and skill gaps that could hinder sustained progress. Ultimately, the analysis underscores the potential for Uzbekistan to achieve upper-middle-income status by 2030 through enhanced innovation management, offering valuable insights for other developing economies seeking to leverage innovation as a catalyst for long-term economic resilience and competitiveness.